Best nerds forever - Patterson, James, 1947-; Grabenstein, Chris; Santoso, Charles (New York : Jimmy Patterson Books, Little, Brown and Company, 2021)
Rendered a ghost by a bicycle accident, young Finn McAllister teams up with fellow spirit Isabella Rojas to commit invisible pranks on the living, before discovering that they cannot move on to the afterlife.
Keywords: Death -- Juvenile fiction; Ghost stories; Detective and mystery fiction